Pedagogical Competence of Science Pre-Service Teachers: Baseline for Training Program - Obispo, Glenn Joseph O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This descriptive survey aimed to explore the pedagogical competence of science pre-service teachers (PSTs). The study involved 35 PSTs in a state university in Central Luzon, Philippines. In accordance to the National Competency-Based Teachers Standard (NCBTS) domains, science PSTs were assessed using an adapted NCBTS survey questionnaire to find out the pedagogical areas they do best and the areas that they have to develop. Results revealed that a typical science PST is a female, aged 21 years old and below from college. The study concluded that the pedagogical competence of Science pre-service teachers is moderately evident in terms of social regard for learning, learning environment, diversity of learners, curriculum, community linkages and personal growth and professional development domain. The findings on this study served as basis in constructing a training program for science PSTs which could enhance their pedagogical competence as they embrace the actual workplace after graduation.